(3HQfGeL JOQjHi deYdeGJ QjGV GdCWaGd dJfejI egGQGJ eG hQGA GdeYQaI (B/ s - (3fQejf SdGeg YHOGdYRjR eMehOs; (3GdSjO YHOGdbGOQ TQja (B: s; (3gjGe jGbhJ SWhMi (B: s ((3GdbGgQI (B: s (3fQejf SdGeg YHOGdYRjR eMehO (B: s, 2016)
(3hgOaJ gPg GdOQGSI Gdi JfejI egGQGJ eG hQGA GdeYQaI dOi eYdeGJ QjGV GdCWaGd(B: (3HGSJNOGe HQfGeL JOQjHi ddeYdeGJ h JchfJ YjfI GdHMK ef (B(30) (3eYdeI ef GdYGedGJ HGdeOGQS GdMchejI h GdQSejI dZGJ YjfI GdHMK YHGQI Yf eLehYI JLQjHjI hGMOI jWHb YdjgG GdGNJHGQ bHdjG h HYOjG(B. (3h GSJNOeJ GdOQGSI GdCOhGJ GdCJjI(B: (3GdHQfGeL GdJOQjHi (B- (3Odjd GdeOQH (B- (3Odjd GdeJOQH(B. (3ebjGS egGQGJ eG hQGA GdeYQaI(B. (3h Je JWHjb GdebjGS bHdjG h HYOjG h JJHYjG Ydi eLehYI GdeYdeGJ (B((3YjfI GdHMK(B). (3h CSaQJ GdOQGSI Yf eLehYI ef GdfJGFL CgegG(B: (3JhLO aQhb PGJ OdGdI EMUGFjI Hjf eJhSWi OQLGJ CaQGO GdeLehYI GdJLQjHjI bHd h HYO JWHjb GdHQfGeL Ydi ebjGS egGQGJ eG hQGA GdeYQaI dUGdM GdJWHjb GdHYOi(B. (3dG JhLO aQhb PGJ OdGdI EMUGFjI Hjf eJhSWi OQLGJ CaQGO GdeLehYI GdJLQjHjI ai GdbjGSjf GdHYOi h GdJJHYi ddHQfGeL Ydi ebjGS egGQGJ eG hQGA GdeYQaIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdJQHjI ddWahdI GdeHcQI (B- (3bSe GdYdhe GdJQHhjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3HQfGeL JOQjHis; (3JfejI GdegGQGJs; (3eYdeGJ QjGV GdCWaGds